Fujitsu, marketing in China. - Ng, Adeline Shu Lin. (2008)
China is an emerging economy, the notebook industry is ever changing and very competitive, replacing the desktop industry, hence it would be interesting to find out more about the dynamics of such a change. Fujitsu is a new entrant into the China market.